UTILIZATION OF ONLINE LIBRARY SERVICES IN INDONESIA - Al Muhdil Karim; Evi Zakiyah (Publication Library and Information Science, 2018)
Abstrack. This study describes the utilization of online library services by the Indonesian community in general. In addition, this article describes what efforts undertaken by the Government of Indonesia through the National Library of the Republic of Indonesia in increasing interest in reading Indonesian society where many issues or research results nuanced read Indonesian story is ranked lower than the other countries. However, the Government of Indonesia is not facing such problems, several plans and innovations have been implemented, namely the development of National Library with an attractive design, making many online services such as Indonesia One Search, KIN, Portal e-resources and so forth. In the last year, people who visited the library exceeded the target, which in 2015, library visitors amounted to 3,676,309 and in 2016 increased to 4,326,475 visitors.